Robust engraftment of fetal nonhuman primate CD34-positive cells in immune-deficient mice. Issue 4 (30th March 2022) - Little, Christopher J; Haynes, William J; Huang, Liupei; Daffada, Cross M; Wolfe, Bryce K; Perrin, Elizabeth; Simpson, John A; Kropp Schmidt, Jenna A; Hinkle, Hayly M; Keding, Logan T; Behrens, Ryan T; Evans, David T; et al.
Abstract: Nonhuman primates (NHPs) represent one of the most important models for preclinical studies of novel biomedical interventions. In contrast with small animal models, however, widespread utilization of NHPs is restricted by cost, logistics, and availability. Therefore, we sought to develop a translational primatized mouse model, akin to a humanized mouse, to allow for high-throughput in vivo experimentation leveraged to inform large animal immunology-based studies. We found that adult rhesus macaque mobilized blood (AMb) CD34+-enriched hematopoietic stem and progenitor cells (HSPCs) engrafted at low but persistent levels in immune-deficient mice harboring transgenes for human (NHP cross-reactive) GM-CSF and IL3, but did not in mice with wild-type murine cytokines lacking NHP cross-reactivity. To enhance engraftment, fetal liver-derived HSPCs were selected as the infusion product based on an increased CD34 hi fraction compared with AMb and bone marrow. Coupled with cotransplantation of rhesus fetal thymic fragments beneath the mouse kidney capsule, fetal liver-derived HSPC infusion in cytokine-transgenic mice yielded robust multilineage lymphohematopoietic engraftment. The emergent immune system recapitulated that of the fetal monkey, with similar relative frequencies of lymphocyte, granulocyte, and monocyte subsets within the thymic, secondary lymphoid, and peripheral compartments. Importantly, while exhibiting a predominantly naïve phenotype, in vitro functional assays demonstrated robust cellular activation in response to nonspecific and allogenic stimuli. This primatized mouse represents a viable and translatable model for the study of hematopoietic stem cell physiology, immune development, and functional immunology in NHPs. Summary Sentence : Engraftment of rhesus macaque hematopoietic tissues in immune-deficient mice yields a robust BLT/NeoThy-type primatized mouse model for studying nonhuman primate hematopoiesis and immune function in vivo. Graphical Abstract: Engraftment of rhesus macaque hematopoietic tissues in immune-deficient mice yields a robust BLT/NeoThy-type primatized mouse model for studying non-human primate hematopoiesis and immune function in vivo.